The Analysis of Vertical Mismatch and Manufacturing Labor Wage by Using Cramer's V Method - Hartato Hartato (Jurnal Public Policy, 2020)
As the leading sector of the national economy through its contribution, the manufacturing industry sector in Indonesia was precisely filled with the dominance of vertical mismatch or mismatch between education levels and types of work based on the 2015 National Labor Force Survey (Sakernas). The negative effects of vertical mismatch have an impact on the low wages earned by labor because investment at the education level is not maximally used when working. This paper aims to study the tendency of vertical mismatch to labor wages in the manufacturing industry sector by training, education level, region, & generation using descriptive analysis methods (crosstabulation & graphics) and Cramer's V to see the correlation with August 2015 Sakernas data. The results of research with the total sample of 1,259 workers shows that vertical mismatch is significantly related to labor wage with the tendency of workers who are overqualified to face low wages. In addition, overqualified workers occur in all regions of Indonesia with the characteristics of younger generations and Diploma IV / S1 graduates. The conclusion of this paper is that industrial labors in Indonesia are still classified as overqualified and experience low wages. The efforts that need to be done are improving the skills of workers through training so as to have a positive effect on mismatch workers to obtain higher wages.